2022
DOI: 10.1049/cth2.12293
|View full text |Cite
|
Sign up to set email alerts
|

Optimal attitude consensus for multi rigid bodies network considered on the lie group SO(3) with connectivity preserving property

Abstract: This paper proposes distributed optimal attitude consensus control for single-integrator multi rigid bodies with undirected network evolving on Special Orthogonal Group SO(3) while simultaneously guarantees the connectivity preservation property for agents using descent gradient algorithm. Since by Use of the Euclidean distance on Lie group as a measure of the energy of the state does not define and preserve the topology of SO(3); besides, solving the Hamilton-Jacobi-Bellman equation in optimal control problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…By using the actor-critic reinforcement learning framework and a non-singular fast terminal sliding mode, an neural network-based fixed-time control strategy is developed for achieving optimal attitude consensus control [20]. Mansourinasab [21] proposes distributed optimal attitude consensus control for single-integrator multi-rigid bodies with an undirected network, while simultaneously guaranteeing the connectivity preservation property for agents using a descent gradient algorithm. Qi [22] addresses the problem of attitude consensus control for multiple rigid spacecraft where only a subset of followers can obtain the leader's state information.…”
Section: Introductionmentioning
confidence: 99%
“…By using the actor-critic reinforcement learning framework and a non-singular fast terminal sliding mode, an neural network-based fixed-time control strategy is developed for achieving optimal attitude consensus control [20]. Mansourinasab [21] proposes distributed optimal attitude consensus control for single-integrator multi-rigid bodies with an undirected network, while simultaneously guaranteeing the connectivity preservation property for agents using a descent gradient algorithm. Qi [22] addresses the problem of attitude consensus control for multiple rigid spacecraft where only a subset of followers can obtain the leader's state information.…”
Section: Introductionmentioning
confidence: 99%
“…Linear matrix inequality (LMI) method is used to solve the optimizations related to the constrained model predictive control (MPC) control of a 3D pendulum on SO(3) in ref. [7]. It is shown that using LMI for solving MPC problem on manifold needs less control efforts than standard MPC.…”
Section: Introductionmentioning
confidence: 99%